2008
DOI: 10.1016/j.jcrs.2007.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of Viscoat and DuoVisc on postoperative intraocular pressure after small-incision cataract surgery

Abstract: Viscoat caused significantly higher IOP increases and significantly more IOP spikes than DuoVisc in the early postoperative period. Therefore, if Viscoat is used during cataract surgery, an additional cohesive OVD should be used for IOL implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…1, 3 We quantitatively compared the residual amount of each OVD on the corneal endothelium of porcine eyes after PEA conducted in the same manner as actual cataract surgery. We found that Viscoat could be dispersed by lower intraocular pressure after the removal of the ultrasound tip.…”
Section: Commentsmentioning
confidence: 99%
“…1, 3 We quantitatively compared the residual amount of each OVD on the corneal endothelium of porcine eyes after PEA conducted in the same manner as actual cataract surgery. We found that Viscoat could be dispersed by lower intraocular pressure after the removal of the ultrasound tip.…”
Section: Commentsmentioning
confidence: 99%
“…1 Ophthalmic viscosurgical devices offer many advantages; however, their use has been correlated with increases in intraocular pressure (IOP) within the first 24 hours postoperatively. [2][3][4][5][6][7] These increases are the most frequent short-term complication of cataract surgery and can lead to corneal edema and pain. In addition, they may increase the risk for retinal artery occlusion, ischemic optic neuropathy, and deterioration of preexisting glaucomatous nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Elevated postoperative IOP is attributed to damage to the trabecular meshwork, inflammation, retained lens material, and clogging of the trabecular meshwork by the OVD substance. [25][26][27] In uneventful cataract surgery, the most important reason for an early postoperative IOP increase may be the residual OVD material, which mechanically obstructs the trabecular outflow pathway and hence decreases the outflow facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when it is not removed completely, it may cause intraoculer pressure (IOP) rise within the first 24 hours following the cataract surgery. [2][3][4][5] There are also other causes which may contribute to elevated IOP after cataract surgery such as retained lens content, iris pigment release and hyphema caused by surgical trauma. 6 Postoperative IOP rise may cause pain, discomfort, corneal edema, optic nerve damage and visual field loss in patients with preexisting glaucoma.…”
Section: Comparison Of Efficacy and Safety Of Topical Dorzolamide-timmentioning
confidence: 99%